Evaluation of Variability in Gait Styles Used by Dogs Completing Weave Poles in Agility Competition and Its Effect on Completion of the Obstacle - Eicher, Logan D.; Markley, Arielle Pechette; Shoben, Abigail; Sundby, Annika E.; Kieves, Nina R. (Frontiers in Veterinary Science, 2021)
Objective: The aim of this study was to evaluate and define paw placement patterns for canines completing the weave pole obstacle during canine agility trials. Secondary objectives were to determine the most efficient running style, completion percentages, and provide a basis for future studies to evaluate long-term implications of variants in weave style and predisposition to injury. We hypothesized that dogs would display definitive gait patterns, and that a single stepping pattern would yield faster run times compared to double stepping patterns. Animals: 1,377 video recordings of dogs completing weaves poles at the AKC 2019 National Agility Championship Procedures: Competition videos were reviewed as dogs attempted completion of the weave pole obstacle. Data collected included front limb and rear limb paw placement styles, time to complete the obstacle, and demographic data. Results: Attempts could be classified into one of five styles based on front and rear paw placement, with no one style dominant. Weave style differed by height and breed with taller dogs and Border Collies preferring a single stepping style. Weave times were significantly faster for competitors using a single stepping style vs. other gaits. Conclusions and Clinical Relevance: This study found five identifiable gait styles used by dogs running weave pole obstacles, with front feet single stepping (FFSS) yielding significantly faster run times compared to other gaits. Clear classification of running styles will allow future studies to evaluate different stresses on joints, such as the shoulder, between varying gait styles, which could lead to recommendations for injury prevention.